Identification of plant growth promoting antagonistic bacteria against blast disease of rice - Haque, MM; Hasna, Mk; Khalil, MI; Nabi, KME; Ferthouse, J; Paul, NR (Bangladesh Journal of Nuclear Agriculture, 2023)
This study aimed to isolate and identify plant growth-promoting bacteria from rhizosphere of rice plants that exhibit antagonistic properties against Magnaporthe oryzae, the causal agent of blast disease. Bacteria were isolated from the surface of rice leaves, stems, and soil attached to the roots. The antagonistic activity of the isolated bacteria was assessed using a dual culture method, and identities were determined through 16S rDNA sequencing. To evaluate their growth-promoting abilities, assays were conducted to measure indole acetic acid (IAA) production, siderophore secretion, hydrogen cyanide (HCN) production, and phosphate solubilization. The results revealed that Bacillus subtilis, identified as BDISO_01R, exhibited antagonistic behavior and the maximum inhibition of M. oryzae (81.00%) was obtained by bacterial isolate BDISO-01R. Additionally, eight bacterial isolates demonstrated IAA production, sixteen isolates produced siderophores, and nine isolates displayed phosphate solubilization capability. This research sheds light on the diverse microbial arsenal that can potentially promote rice growth while combating blast disease. Bangladesh J. Nuclear Agric, 37(1): 63-79, 2023